Homo and heteropolymetallic Group 4 molecular nitrides. Issue 41 (30th September 2015) - Caballo, Jorge; Greño, Maider; Mena, Miguel; Pérez-Redondo, Adrián; Yélamos, Carlos
Abstract : A trichloride zirconium complex reacts with [M(C5 H5 ) x ] via metathesis of chloride ligands while [K(C5 Me5 )] causes the one-electron reduction of a titanium nitrido metalloligand. Abstract : Treatment of [{Ti(η 5 -C5 Me5 )(μ-NH)}3 (μ3 -N)] (1 ) with zirconium or hafnium tetrachloride adducts [MCl4 (thf)2 ] affords complexes [Cl3 M{(μ3 -N)(μ3 -NH)2 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (M = Zr (2 ), Hf (3 )). Titanium chloride complexes [Cl2 Ti{(μ3 -N)2 (μ3 -NH)Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (4 ) and [(Me2 NH)ClTi{(μ3 -N)3 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (5 ) are obtained by reaction of1 with [TiCl4− x (NMe2 ) x ] ( x = 2, 3). The dimethylamine ligand in5 is displaced by pyridine to give the analogue complex [(py)2 ClTi{(μ3 -N)3 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (6 ). Treatment of the titanium chloride complexes4 and5 with sodium cyclopentadienide or lithium bis(trimethylsilyl)amide reagents leads to the cube-type nitrido derivatives [RTi{(μ3 -N)3 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (R = η 5 -C5 H5 (7 ), N(SiMe3 )2 (8 )). The reaction of the zirconium trichloride complex2 with [Tl(C5 H5 )] yields exclusively the dichloride-monocyclopentadienyl derivative [(η 5 -C5 H5 )Cl2 Zr{(μ3 -N)(μ3 -NH)2 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (9 ). However, the treatment of2 with excess [Na(C5 H5 )] causes further chloride replacement in9 and subsequent cyclopentadiene elimination to give [(η 5 -C5 H5 )Zr{(μ3 -N)3 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (10 ) via intermediates [(η 5 -C5 H5 )2 ClZr{(μ3 -N)Ti3 (η 5 -C5 Me5 )3 (μ-NH)2 (μ3 -N)}] (11 ) and [(η 5 -C5 H5 )ClZr{(μ3 -N)2 (μ3 -NH)Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (12 ). Treatment of2 or9 with [Mg(C5 H5 )2 ] leads to the magnesium derivative [(η 5 -C5 H5 )Mg(μ-Cl)2 (η 5 -C5 H5 )Zr{(μ4 -N)(μ3 -N)(μ3 -NH)Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (13 ), which can be visualized as a result of the incorporation of one [Mg(η 5 -C5 H5 )Cl] moiety to complex12 . In contrast to the metathesis process with [M(C5 H5 ) x ] derivatives and subsequent C5 H6 eliminations, the reaction of2 with potassium pentamethylcyclopentadienide in toluene produces the paramagnetic derivative [K(μ-Cl)3 Zr{(μ3 -N)(μ3 -NH)2 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (14 ) and C10 Me10 . Complex14 reacts with one equivalent of 18-crown-6 or cryptand-222 to give the molecular complex [(18-crown-6)K(μ-Cl)3 Zr{(μ3 -N)(μ3 -NH)2 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (15 ) or the ion pair [K(crypt-222)][Cl3 Zr{(μ3 -N)(μ3 -NH)2 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (16 ). The X-ray crystal structures of2, 8, 13 and15 have been determined.